2021
DOI: 10.1002/its2.8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of natural herbicides on dandelion (Taraxacum officinale G.H. Weber ex Wiggers) and white clover (Trifolium repens L.) populations

Abstract: Perennial broadleaves such as dandelion (Taraxacum officinale G.H. Weber ex Wiggers) and white clover (Trifolium repens L.) are known to be pervasive weeds in stands of maintained turfgrasses. The use of synthetic herbicides is the most common and effective method of control for these weeds. As pesticide use in European countries, Canada, and the United States is becoming more scrutinized, identification of alternative weed control options may be necessary. However, few organic or natural weed control products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Certain products also caused short-term (1 to 2 weeks) undesirable turf phytotoxicity. Other research has found similar, non-chemical products have caused injury to desired turf as well [8,11]. Similar visual burndown is often observed after applying non-selective herbicides such as glyphosate, diquat, or glufosinate [3].…”
Section: Discussionmentioning
confidence: 69%
“…Certain products also caused short-term (1 to 2 weeks) undesirable turf phytotoxicity. Other research has found similar, non-chemical products have caused injury to desired turf as well [8,11]. Similar visual burndown is often observed after applying non-selective herbicides such as glyphosate, diquat, or glufosinate [3].…”
Section: Discussionmentioning
confidence: 69%
“…In light of PA's potential as a bio-herbicide and its ability to contribute to the reduction of synthetic herbicides, researchers have been exploring its efficacy, and have shown that PA is the most successful bio-herbicide available (Webber et al, 2014a;Carroll et al, 2022;Muñoz et al, 2022;Pannacci et al, 2022). However, its effectiveness varies between weed species (Webber et al, 2014a;Webber et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…dates back to the 1910s (Hansen 1918). Other acids, such as acetic, pelargonic, and sulfuric, have demonstrated efficacy for weed control (Aslander 1927;Carroll et al 2020;Crafts 1933Crafts , 1960. Crafts (1960) reported that sulfuric acid can serve as a selective herbicide to kill broadleaf weeds in cereal crops.…”
Section: Introductionmentioning
confidence: 99%
“…The author noted that the use of 5% and 20% acetic acid for weed control would cost an estimated US$1,107 and US$4,426 per hectare, respectively. Recently, Carroll et al (2020) reported that horticultural vinegar containing 30% acetic acid applied at 374 L ha −1 controlled white clover and dandelion (Taraxacum officinale G.H. Weber ex Wiggers) in perennial ryegrass (Lolium perenne L.) turf, but it also injured the turfgrass.…”
Section: Introductionmentioning
confidence: 99%